Moderating Islamic Education through the Digital Literature Movement in Madrasah - Idris Akbar Pramono; Sugiyar (ELITE Association Indonesia, 2023)
The era of the Industrial Revolution 4.0 is marked by the massive development of information technology and the ease with which information can be spread without any filter, this convenience is used by certain circles to spread and propagate extreme religious understanding. This study aims to examine the urgency of digital literacy in order to seek moderation of Islamic education. The method used in this study is a literature review with content analysis techniques. The conclusion of this study is that digital literacy skills are very important in efforts to moderate Islamic education, as a preventive effort in warding offintolerance and dangerous understanding in the name of religion, so it needs to be developed in the madrasah environment. Basicand advanced digital literacy competencies that need to be trained and promoted are summarized in ten stages, namely: accessing, selecting, understanding, analyzing, verifying, evaluating, distributing, producing, participating, and collaborating Keywords:literacy, digital, Islamic moderation, education